2018
DOI: 10.1038/s41433-018-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the macular pigment in AMD: the past, the present, and the future

Abstract: Carotenoids are lipophilic isoprenoid pigments with a common CH core chemical structure that are naturally synthesized by many plants, algae, bacteria, and fungi. Humans and animals cannot synthesize carotenoids de novo and must obtain them solely through dietary sources. Among the more than 750 carotenoids in nature, only lutein, zeaxanthin, meso-zeaxanthin, and their oxidative metabolites selectively accumulate in the foveal region of the retina where they are collectively referred to as the macular pigment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 88 publications
4
58
0
Order By: Relevance
“…Carotenoid macular bioavailability is influenced by various factors, but studies showed that carotenoid incorporation in the macula is mainly based on lipoprotein transport mechanisms such as IRBP, requires a minimal diet intake of fat and that polyunsaturated fatty acid-rich diet improves absorption of carotenoids. [44][45][46] suggested a link between macular pigment delivery system through Müller glial cells and the formation of drusen. We may hypothesize that, despite the established benefit of L/Z supplementation to the foveal vision, there may be a price to be paid for the delivery of L/Z to the fovea, namely a higher lipid uptake in the RPE and the retina, which then must be discarded as drusen or SDD.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoid macular bioavailability is influenced by various factors, but studies showed that carotenoid incorporation in the macula is mainly based on lipoprotein transport mechanisms such as IRBP, requires a minimal diet intake of fat and that polyunsaturated fatty acid-rich diet improves absorption of carotenoids. [44][45][46] suggested a link between macular pigment delivery system through Müller glial cells and the formation of drusen. We may hypothesize that, despite the established benefit of L/Z supplementation to the foveal vision, there may be a price to be paid for the delivery of L/Z to the fovea, namely a higher lipid uptake in the RPE and the retina, which then must be discarded as drusen or SDD.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidants used for the treatment in this study are L-Z, which can neutralize reactive oxygen species to counter oxidative damage in retinal cells in many eye disorders [23, 5356]. In addition, our previous study showed that L-Z reduce ERS in light-induced retinopathy [34].…”
Section: Discussionmentioning
confidence: 99%
“…An anatomical structure in the retina of the human eye particularly rich in carotenoids is referred to as the macula lutea or the yellow spot, due to its intense colouration . Three polar carotenoids, called xanthophylls, have been identified in the macular pigment pool, namely, lutein (Lut), zeaxanthin (Zea) and meso ‐zeaxanthin ( m ‐Zea) (see Figure ) . Resonance Raman spectroscopy of macular xanthophylls can be effectively applied to examine their properties in the natural system or even for imaging the retina, owing to the relatively strong Raman scattering signal of polyene dyes .…”
Section: Introductionmentioning
confidence: 99%